1986
DOI: 10.3181/00379727-181-42224
|View full text |Cite
|
Sign up to set email alerts
|

Development of Vaginal Adenosis-like Lesions and Uterine Epithelial Stratification in Mice Exposed Perinatally to Diethylstilbestrol

Abstract: Abstracf. Pregnant ICR/JCL mice were given either four daily subcutaneous injections of 20-2000 pg diethylstilbestrol (DES)/day or a 4-day intravenous infusion of 20-200 pg DES/day starting on Day 15 of gestation. Female mice were injected with 0.01-50 pg DES/day for 5 days starting on the day of birth. Females given oil injections during the neonatal period and offspring of mothers given injections of an infusion of respective vehicles alone served as controls when corresponding ages were attained. Incidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
17
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…Haematoxylin and eosinstained sections of DES-exposed and Wnt7a −/− FRTs displayed lesions including Wolffian duct (w) remnants (a,b). Wnt7a −/− FRTs displayed concretions (con) forming in the vaginal fornices (c) and epithelial inclusions in the vagina stroma (adenosis, d), lesions that have been described in DES-exposed mice 9,11,12 . e, Control (oil treated) uteri had simple columnar epithelium (inset), stroma (s) populated by glands (g) and compact layers of smooth muscle (h).…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…Haematoxylin and eosinstained sections of DES-exposed and Wnt7a −/− FRTs displayed lesions including Wolffian duct (w) remnants (a,b). Wnt7a −/− FRTs displayed concretions (con) forming in the vaginal fornices (c) and epithelial inclusions in the vagina stroma (adenosis, d), lesions that have been described in DES-exposed mice 9,11,12 . e, Control (oil treated) uteri had simple columnar epithelium (inset), stroma (s) populated by glands (g) and compact layers of smooth muscle (h).…”
mentioning
confidence: 99%
“…DESexposed mice had shallow vaginal fornices, malformed oviducts that lacked coils, Wolffian duct remnants (Fig. 1a), vaginal concretions and adenotic lesions in the vagina 9,11,12 . Wnt7a −/− mice also had shallow vaginal fornices (data not shown) and malformed oviducts 8 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Our results indicated that DES altered the expression levels of Dnmts and DNA methylation. [3][4][5], and DES is now widely known as an estrogenic endocrine disruptor. In our previous studies, we showed that mice treated neonatally with DES or the phytoestrogen, genistein, developed altered expression levels of various genes in male reproductive organs, even during adulthood [6][7][8][9][10].…”
mentioning
confidence: 99%